GREEN ACCOUNTING IN PRACTICE: COMPARATIVE COST ANALYSIS OF MANAGEMENT AT A KUPANG HOSPITAL - Beatrix Yunarti Manehat; Yolinda Yanti Sonbay; Leopold Melkiano Triangga Dawu; Maria Bernadethe Mawarni Gelu Wutun; Chantika Elisabeth Hermanus (Jurnal Akuntansi Kontemporer, 2025)
Research Purposes. This study evaluates the comparative costs of using incinerators and third-party services in medical waste management at Hospital X. Research Methods The research employs a qualitative approach through interviews, observations, and document analysis. Research Results and Findings The findings reveal that since the incinerator malfunctioned in 2020, Hospital X has lost up to IDR 22.5 billion in revenue over five years and has incurred costs ranging from IDR 359.6 million to IDR 539.4 million for third-party services. Without an operational incinerator, waste management costs have increased, and revenue losses have persisted. Therefore, investment in repairing or procuring an incinerator is recommended to enhance waste management efficiency and ensure the hospital's financial sustainability. The implications of these findings reveal that dependence on third-party waste management leads to substantial cost burdens and long-term revenue loss. A strategic implication is the need for hospitals to reinvest in incinerator facilities to enhance cost efficiency, support sustainable waste policies, and ensure regulatory compliance.